Preparation and Characterization of Chemical Structure Composition of Polyurethane’s Microcapsules Pesticides - AHMADI, ABBAS (Asian Journal of Chemistry, 2010)
Microencapsulation of pesticides and other agrochemical compounds has been performed for some years. In general, the object of producing such compositions has been to provide controlled release of the active ingredients and particularly to provide a release for longer term efficacy so that it is released over a period of time and is available throughout the effective period. This is particularly significant for pesticides or other ingredients, which are degraded or decomposed over a relatively short period of time or under certain environmental conditions. In general, microencapsulated forms of pesticides are mostly produced by interfacial polymerization and the microcapsule walls are formed from polymeric material. In this paper, we have produced the microcapsulated form of chloropyrifos (one of the high usage solid phosphorus insecticides) and fenitrothion (one of the high usage liquid insecticides) in the lab and bench scale by use of interfacial polymerization by polyurethane. We changed some ofthe conditions (temperature, stirring rate and time) and found the better of them and also obtained the size of particles, the release of pesticides in a period of time, the graph of particle size distribution and the SEM images of particles.